Sustaining Social Harmony: Exploring Community Cohesion through the Kondowa-Dongkala Village Festival in Buton - Laxmi, Laxmi; Hermina, Sitti; Aris, La Ode; Koodoh, Erens E.; Zainal, Zainal (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
The traditional village festival demonstrates the essence of unity values, catalyzing social cohesion within the community. Various cultural manifestations, such as customary deliberations, traditional ceremonies, and local arts performances, signify the underlying social system. This study aims to elucidate the social cohesion among the Kondowa-Dongkala community through the village festival in Buton. Employing a qualitative research method, data were collected through in-depth interviews with key informants, including Parabela Anamohane and local community members actively involved in the festival proceedings. The findings reveal that the village festival is an annual event, preceded by a village deliberation to establish customary laws governing community behavior on land and sea. Conservation efforts are evident in prohibiting marine resource extraction within the kaombo area for one year, followed by communal utilization during the festival. Each night is marked by local art performances featuring traditional drumming and dances by various age groups, underscoring the village festival's cultural richness and social cohesion.